Phenomenon Endowment in Arabic - Dr. Adulwahb Ibrahim Elmhroog (Journal of Scientific and Human Dimensions, 2026)
An Phenomenon l knew her Arabic since Its origin And he knew About the Arabs They They don t start Basakin And they do not stop On a moving That’s Iightness Stillness And the endowment Against connection Therefore Waqf (endowment) has different aspects several she: Stopping with a pause, And the Romans, And with the nasalization And by transport , By doubling, And it has been shown This phenomenon Scholars of Tajweed And the voices, And we showed its Iocations So she adorned herself with it Arabic And increased its splendor, He participated in detail This phenomenon Scintists Grammar And the exchange And the voices and Tajweed.